TEOREMA AMPLOP DAN DUALITAS - Tony S Chendrawan (FEB Universitas Sultan Ageng Tirtayasa, 2017)
Economic model is a theoretical construction or economic analysis framework consisting of a set of concepts, definitions, assumptions, equations, similarities (identities) and inequalities from which conclusions will be derived. Duality theory is one of the important and interesting concepts of linear programs in terms of theory and practice, the background is that every linear problem of programming, always has a second problem which is always related to the first problem. The first problem is called Primal and the second problem is called Dual. The two problems are always related in such a way that the optimal solution to the first problem will provide complete information about the optimal solution to the second problem. The relationship between the original model problem (called the